A general theory for the lifetimes of giant molecular clouds under the influence of galactic dynamics - Jeffreson, Sarah; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We propose a simple analytic theory for environmentally dependent molecular cloud lifetimes, based on the large-scale (galactic) dynamics of the inte